1973
DOI: 10.1063/1.1679790
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric investigation of the dissociation energy of the molecule AlAu and estimated bond energies of some diatomic intermetallic compounds with gold

Abstract: High-temperature Knudsen-cell mass spectrometry has been used to measure the gaseous equilibria over an aluminum-gold or aluminum-silver-gold alloy in a tantalum cell. The enthalpies for the reactions (1) AlAu(g) = Al(g) + Au(g), and (2) AlAu(g) + Au(g) = Au2(g) + Al(g) were measured. The following dissociation energy D°0, heat of sublimation Δ H°s,298, and heat of formation Δ H°f,298 were derived from these reaction enthalpies for gaseous AlAu: 77.0 ± 1.5, 98.4 ± 2.5, and 88.9 ± 2.0 kcal mole−1, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 18 publications
4
7
0
Order By: Relevance
“…Its equilibrium bond length is 2.39 Å, which overestimates the measured value 2.34 Å. However, the calculated vibrational frequency 318 cm −1 and dissociation energy 3.48 eV fall close to experimental results of 330 cm −1 and 3.37 ± 0.13 eV [44,45]. For AuSi, its theoretical results of bond length 2.28 Å and dissociation energy 3.17 eV are in good agreement with available experimental data 2.26 Å [46] and 3.16 eV [47].…”
Section: Theoretical Methods and Computational Detailssupporting
confidence: 68%
“…Its equilibrium bond length is 2.39 Å, which overestimates the measured value 2.34 Å. However, the calculated vibrational frequency 318 cm −1 and dissociation energy 3.48 eV fall close to experimental results of 330 cm −1 and 3.37 ± 0.13 eV [44,45]. For AuSi, its theoretical results of bond length 2.28 Å and dissociation energy 3.17 eV are in good agreement with available experimental data 2.26 Å [46] and 3.16 eV [47].…”
Section: Theoretical Methods and Computational Detailssupporting
confidence: 68%
“…The diatomic AuAl has a C ∞ v symmetry with the calculated vibrational frequencies of 332.6 cm –1 , which is in excellent agreement with the experimental results of 333 cm –1 . The ground-state geometry of the Al 2 Au 2 cluster has a tetrahedral structure with the C 2 v symmetry, identical to the experimentally identified structure by high-resolution PES .…”
Section: Resultssupporting
confidence: 84%
“…Colloquially known as “superatoms”, some Al clusters have been found to behave analogously to the halogen, alkaline earth, and other multivalent species . Alloyed Au x Al y clusters have been actively explored, and a rich spectrum of structures was discovered, ranging from Au-rich Au 5 Al to Al-rich AuAl 12 , through various techniques including photoelectron spectroscopy (PES), high-resolution photoelectron imaging, and first-principles calculations. In this group, the clusters with (nearly) equal compositions, i.e., x ≈ y , were relatively less studied until the recent discovery of Al 2 Au 2 , followed by a series of new alloyed clusters Au x Al y – ( x + y = 7, 8; x = 1–3; y = 4–7) . Motivated by these new findings, in this paper, we theoretically investigated the Au n Al n clusters, where the Al and Au have equal compositions, in the range n = 2–10.…”
Section: Introductionmentioning
confidence: 99%
“…After the geometry optimizations were performed, it was found that the dopant atoms had not distorted the tube like structure of Au 42 and still formed a linear chain at the centre of the tube. In the Au doped Au 48 cluster, it was found that similar to the case of Au 3 Au 24 , one of the gold atoms lying at the central axis had moved to form a rhombus at one end of the tube, while the rest 1.95 1.67 57,59 of the Au atoms formed a chain. Interestingly, as Fig.…”
Section: Resultsmentioning
confidence: 87%